"It's so tough for us now" – COVID-19 has negatively impacted religious practices relating to death among minority ethnic groups. (May 2021) - Routen, A.; Darko, N.; Willis, A.; Miksza, J.; Khunti, K.
Abstract: Objective: The aim of the study was to investigate the impact of the COVID-19 pandemic and prevention measures on religious practices after death, by ethnic grouping, in an opportunistic/convenience sample of UK adults. Methods: We distributed a questionnaire online and in hard copy between May 1 and June 18, 2020, via social media, post and face-to-face contact in Leicester, a multi-ethnic city in the UK. Results: From 980 adults providing consent, 665 completed some or all survey items and provided ethnicity data. More than double the proportion of Black and South Asian individuals reported religious practices relating to death, burials or funerals being affected by COVID-19 than White groups. Of the 151 participants reporting practices being impacted, a greater proportion of ethnic minority groups reported restricted access/alteration to eight death-related practices (e.g., funeral attendance) compared with White groups (significantly different for all practices, P  < 0.05). Conclusion: The initial phase of the COVID-19 pandemic in the UK has negatively impacted on the ability to conduct religious practices after death in all ethnic groups, but the impact appears greater in ethnic minority populations than in White groups. There is a need for further qualitative research on the impact of the COVID-19 pandemic on death and burial practices of minority ethnic groups.